Pengembangan Modul Digital Kewirausahaan Berbasis Project-Based Learning Untuk Mahasiswa JTIK - Iqra Choirunisa Ahmad; Satria Gunawan Zain; Fadhlirrahman Baso; Alimuddin Sa’ban Miru; Irwansyah Suwahyu (Progressive Information, Security, Computer, and Embedded System, 2026)
This study aimed to develop a Project-Based Learning (PjBL)-based digital entrepreneurship module for students of the Informatics and Computer Engineering Department and to determine the validity and practicality of the developed module. This research employed the Research and Development (R&D) method using the Four-D (4D) development model consisting of the define, design, develop, and disseminate stages. Data were collected through observation, interviews, and questionnaires involving material experts, media experts, and students of the Informatics and Computer Engineering Department, Universitas Negeri Makassar. The results showed that the developed module obtained a material validity score of 98.89% and a media validity score of 98.79%, both categorized as very valid. Furthermore, the practicality test results showed scores of 84.12% in the small-group trial and 86.84% in the large-group trial, which were categorized as very practical. The module was developed using Canva and presented in an interactive flipbook integrated with Quizizz to support more engaging and interactive project-based entrepreneurship learning. Therefore, the developed digital entrepreneurship module is feasible to be used as a learning material in technology-based entrepreneurship learning.